Стабілізація ефективного управління ліквідністю банків - Аванесова, Н. Е.; Сідлецька, Я. Г. (НТУ "ХПІ", 2014)
Одним із пріоритетних завдань центральних банків є управління ліквідністю банківської системи. В свою чергу актуальність управління ліквідністю досить широко розповсюджена серед учених. У статті були розглянуті чинники, що сприяють ефективному управлінню ліквідністю банків, визначено економічну сутність ліквідності банку, проаналізовано стратегії управління банківською ліквідністю, запропоновано заходи щодо ефективного управління ліквідністю.

One of foreground jobs of central banks is a management by liquidity of the banking system. In turn management actuality widely enough widespread liquidity among scientists. As a result of researches some approaches were educed. Studying this subjects wider, we chose next two conceptual approaches: after process approach management by liquidity of bank is the continuous process of analysis, planning, control and adjusting of liquidity of bank on the basis of application of certain tool not only with the purpose of combination of indexes of maximization of profitability and obligatory observance of norms of liquidity but also for the receipt of positive results; at approach of the systems management by liquidity is the organized, well-organized totality of elements and intercommunications between them, that develop constantly. Also considered factors that assist an effective management liquidity of banks, economic essence of liquidity of bank is certain, management strategies are analyzed by bank liquidity, the events of relatively effective management offer liquidity.
Stabilizing of effective liquidity management of banks
Keywords: банківська система; ризик ліквідності; стратегії управління ліквідністю; фінансова стійкість; banks; liquidity; liquidity risk; liquidity management strategies; liquidity management of banks